Theorizing Situated Inequality in Everyday School Life in a Marginalized Residential Area - Sylvest-Berg, Rebekka; Tybjerg, Gry (International Review of Theoretical Psychologies, 2026)
In this article, we examine inequality at a school located in a marginalized residential area of a larger Danish city, using the theoretical concept of ‘situated inequality’. We argue for theorizing inequality as situated, emerging from how participants collectively manage and navigate coherent, conflictual social situations in their everyday lives. This contrasts with perspectives that view inequality as something predetermined and static that young people “bring with them” to school due to their social backgrounds. Based on fieldwork carried out at the local school, we found that both teachers and young people in the school struggle to develop opportunities of participation under contradictory conditions. This often manifests as conflicts within the classroom. To explore how dynamics of inequality develop, we follow processes of conflicts at the local school, and they become a lens to explore unequal conditions for the young people. Here, we analyze how broader political and societal conflicts are connected to – and in different and shifting ways – matters in the conflicts situated in the everyday school life. When conflicts escalate, the exploration of the conditions for the young people’s participation sometimes disappears due to what we term a ‘strategy of avoidance’. This strategy can, against its intention, become trapped in a circularity of conflicts, where young people in school are singled out as problem carriers due to the marginalized residential area in which they live. We conceptualized such processes of problem placement as a form of ‘collective area categorization’.